The Global Agri-food Sector and the Case of the Tuna Industry: Global Regulation and Perspectives for Development - Bonanno, Alessandro; Constance, Douglas (The International Journal of Sociology of Agriculture and Food, 2021)
Employing the case of the global tuna fish industry, the paper investigates the effect of globalization on political institutions and social agents. Three interrelated points are argued. First, it is maintained that while the process of globalization is pervasive, it is also flexible, i.e. the outcomes of globalization are contested and no particular agent has total control. Second, in the domestic arena the regulatory ability of the nation-state has to be redefined. Third, despite possibilities for some subordinate groups to advance, weak segments of the labor force, particularly in developing countries such as in Latin America, continue to be marginalized. A possible alternative strategy call for attempts to establish international solidarity. The latter, however, should be based on awareness of the limits of protectionist and/or domestic center strategies in the global era.